A vector that replicates as a plasmid and can be efficiently selected in B-lymphoblasts transformed by Epstein-Barr virus. - Sugden, B (1985)
Epstein-Barr virus (EBV) transforms human B-lymphocytes into proliferating blasts which are efficiently established into cell lines. The viral DNA in these cell lines is usually present as complete, unintegrated plasmid molecules. A cis-acting element of EBV, oriP, permits plasmid maintenance in adherent cells that carry EBV DNA. We constructed a vector, pHEBo, that carries oriP and showed that it is also efficiently maintained as a plasmid when introduced into EBV-transformed B-lymphoblasts. The pHEBo vector carries the coding sequences for the hph gene from Escherichia coli such that it can be expressed in mammalian cells and confers resistance to the antibiotic hygromycin B. Hygromycin B kills EBV-transformed lymphoblasts at concentrations of 50 to 300 micrograms/ml. The combination of oriP plus the expressed hph gene makes pHEBo useful for the stable introduction of genes on plasmids into EBV-transformed lymphoblasts. Because pHEBo is derived from the plasmid pBR322 it can be easily isolated from lymphoblasts by reintroduction into E. coli.